2021
DOI: 10.1016/j.adro.2021.100652
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Single-Fraction Stereotactic Ablative Radiation Therapy for the Treatment of Thoracic and Abdominal Oligometastatic Disease With Online Adaptive Magnetic Resonance Guidance

Abstract: Purpose Although SABR can improve oncologic outcomes for patients with oligometastatic disease, treatment of metastases near critical organs remains challenging. The purpose of this study is to determine the dosimetric feasibility of delivering magnetic resonance imaging (MRI)-guided adaptive SABR in a single fraction for abdominal and thoracic metastases. Methods and Materials Previously delivered MRI-guided radiation therapy plans for 20 patients with oligometastatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…These platforms also include dedicated software to enable proactive daily on-table plan adaptation, which eliminates the treatment delay associated with reactive, offline plan adaptation. Planning studies have shown dosimetric improvements with daily online plan adaptation, and early reports from clinical trials on prostate SABR performed using these new devices have suggested good toxicity outcomes [6][7][8].…”
mentioning
confidence: 99%
“…These platforms also include dedicated software to enable proactive daily on-table plan adaptation, which eliminates the treatment delay associated with reactive, offline plan adaptation. Planning studies have shown dosimetric improvements with daily online plan adaptation, and early reports from clinical trials on prostate SABR performed using these new devices have suggested good toxicity outcomes [6][7][8].…”
mentioning
confidence: 99%
“…Both CTgART and MRgART can improve the dosimetric therapeutic index across diverse disease sites and clinical scenarios, with growing clinical evidence for safety and early efficacy supporting ART’s continued use [26] , [32] , [33] , [34] . In particular, several in silico studies have shown that the use of ART has the ability to resolve OAR constraints, improve target coverage, or do both simultaneously [10] , [26] , [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, treatment of both primary and oligometastatic lesions in the thorax to ablative doses is complicated by the adjacency to sensitive OARs and unpredictable intra-fractional motion [ 28 ]. The thorax is a dynamic environment of a beating vascular system, a constricting esophagus, and a bellowing diaphragm.…”
Section: Thoracic Malignanciesmentioning
confidence: 99%